(untitled) (Raparin Journal of Humanities (RJH), 2024)
The Islamic scholars have made wonderful efforts to clarify the religious texts and guide Muslims, some of whom we know their names and lives generation after generation, such as the four Imams and others, and some of them are known very little, and this is contained throughout the Islamic World, we are familiar with many of these scholars that we do not know much information about them. Sheikh Abdel Fattah is also known for his writings and works in the scientific area, and in a certain scope, however, should search and work for his heritage to contribute to the knowledge of his life and efforts more, and when I reviewed the writings of him, I have found that he has written in varied topics. Among them, I saw the works of the Sheikh in his message of "Intimacy among Muslims" and a message also about (Imamate-the Leadership). I took the work, and began to read it carefully, so I looked between the corridors of its lines, and entered into the depth of its words, and realized that there are written words spoken clearly. However, there are veiled wishes that are not spoken, which the reader feels contemplation and reflection, such as his love for the unity of Muslims, and respect for the opposite, these issues have taken their place in my heart, especially in our days when we are in dire need to reconsider our attitudes towards opponents of Muslims, as well as our need to have the morals of the scholars of the Salaf (our ancestors) when disagreeing, and not to allow the difference to turn into conflict and accuse the opposite, the unfortunate thing that we see in our days with our own eyes, and therefore we chose the aforementioned title to be a step and an attempt to stop what we see today of the misbehavior of some Muslims towards their fellow Muslims because of their differences in matters in which the difference is justified.